DINAMIKA RESILIENSI PADA ORANG DENGAN LUPUS (ODAPUS) - Bio Rama Adiputra (Faculty of Psychology, Diponegoro University, 2023)
Lupus is a chronic autoimmune disease in which an abnormal immune system can cause inflammation on several organ or body systems. The risk of mortality rate caused by Lupus is high and late diagnosis is also prevalent which impact the psychological aspect of individual affected with Lupus (so-called Odapus). Therefore, resiliency is needed; that is individual ability to survive and keep optimistic attitude towards recovery. This study aims to describe the resilience dynamics of the affected individuals with Lupus. This is a qualitative study that involved 3 Odapus as participants. There are 1 male and 2 females that have diagnosed Lupus since their age was 15-17 years. The results indicated that partcipants have been developed the resilience skills for their good to copes and deals with various problems which resilience is not just something that adhered in someone, but it is a result of learning process.